DESENTRALISASI PEMOLISIAN DAN PRAWACANA REPOSISI KELEMBAGAAN POLISI - Nur Yahya (Perspektif, 2007)
Change of strategic environment and its life place habitat police have to become especial consideration to police for the reposition of its institute. Position institute of Police continue to be talked to rind its place which more precise. With burden considering analyse duty having equality with duties governance of public which diemban by Domestic Department, and also current strength decentralize and by studying more emphasizing at police culture local accountabilities hence position institute of Police precisely if returned under conducting Ministry of Home Affairs.